The health-related quality of life for hemiarthroplasty and total hip arthroplasty in the elderly: A meta-analysis - Su, Yaping; Li, Ruiling; Ren, Xiangying; Wang, Yuanyuan; Bai, Xiaolu; Zhang, Yurui; Han, Lingyu; Wang, Yiman; Liang, Ran (Frontiers in Medicine, 2023)
Abstract: Purpose The optimal surgical plan for femoral neck fractures(FNFs) in elderly is controversial. European quality of life 5-Dimension Questionaire (EU-5Q) is an international scale, it is used to measure the health-related quality of life (HRQoL) after surgery. We aim to verify the hip arthroplasty effect in elderly by analyzing HRQoL scores in EU-5Q scale. Methods It searched the Ebsco, Emtree, PubMed, Ovid, Cochrane Library, Web of Science databases using strict searching from established to November 30, 2022; used the Cochrane Library's Risk of Bias Assessment Tool and the Newcastle-Ottawa Scale to evaluate the literature; and used RevMan5.4.1 software to perform a meta-analysis. All the included studies had used EU-5Q scale to validate the overall outcomes for elderly hip arthroplasty. Results The final included literature composes of four RCTs, two cohort studies, three case-control trials, and three cross-sectional surveys. This study compared HRQoL scores measured by EU-5Q scale, including 328 elderly patients with total hip arthroplasty (THA) and 323 elderly patients with hemiarthroplasty, which is statistically significant (OR=0.05; 95% CI, 0.02 0.08; P=0.002). One subgroup is unipolar vs bipolar and cemented vs uncemented hemiarthroplasty (OR=0.06; 95% CI, 0.03 0.08; P<0.001). And one subgroup is follow-up time and age arthroplasty (OR=0.16; 95% CI, 0.11 0.22; P<0.001). Another subgroup is molecular exercise and enhanced recovery after surgery (ERAS) subgroup (OR=0.02; 95% CI, -0.03 0.07; P=0.38). The other subgroup is analysis of hemiarthroplasty with cognitive dysfunction vs normal group (OR=0.17; 95% CI, 0.08 0.26; P<0.001). The outcome analysis was consistent with the included studies, HRQoL of the EU-5Q scale is sensitive to surgical outcome between THA and hemiarthroplasty. Conclusion Surgeons still need to further evaluate and verify whether the elderly hip arthroplasty surgical program or effect is optimal. Hemiarthroplasty operation in elderly has pointed a new direction in the clinical treatment, and HRQoL scores measured by EU-5Q can sensitively reflect the rehabilitation status after hip arthroplasty surgery. And extensive correlation between surgical outcomes and perioperative neurocognitive functional should be further investigated.